2014
DOI: 10.1063/1.4880936
|View full text |Cite
|
Sign up to set email alerts
|

Continuous controllable amorphization ratio of nanoscale phase change memory cells

Abstract: The controllable heat behavior, including heat generation and dissipation, is one of the most important physical problems of nanoscale phase-change memory (PCM). A method based on heat accumulation effect to control heat behavior by synthetically modulating the three parameters of applied double pulses is proposed to achieve any expected amorphization ratio. A compact model of nanoscale PCM cells is used to simulate the thermal behavior and amorphization ratio under the condition of single parameter and multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…5c ) can be used to control the addition and homogenization of defects respectively. It is important to note here that multiple resistance states in PCM reported in earlier works 30 31 32 33 34 were created by controlling the relative volumes of the amorphous and crystalline states, the only two physically different states, and are fundamentally different from the multiple resistance states in this work.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…5c ) can be used to control the addition and homogenization of defects respectively. It is important to note here that multiple resistance states in PCM reported in earlier works 30 31 32 33 34 were created by controlling the relative volumes of the amorphous and crystalline states, the only two physically different states, and are fundamentally different from the multiple resistance states in this work.…”
Section: Resultsmentioning
confidence: 88%
“…The recent discoveries of localization effects 35 and defect-templated amorphization 18 in Ge–Sb–Te alloys suggests that defect-engineering approach could be applied to other well-known PCMs too. In addition, with our demonstration of scaling of switching properties in the defect-based approach and multistate switching, we believe that nanoscale PCM structures (mushroom, sidewall, pillar or confined architectures) 5 36 engineered into electronic states in crystalline phase that show localization behaviour in transport will be promising for ultralow-power memories and novel computation strategies 29 30 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The phase transition of GST is a thermodynamic process. The crystallization temperature ( T c ) and melting temperature ( T m ) of GST are reported to be 160°C and 600°C ( Terao et al., 2009 )( He et al., 2014 ). To achieve full crystallization especially in a large area, the heating process takes a relatively long time and the temperature has to be kept beyond T c and below T m .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that the resistance of PCM can be modulated by voltage pulses with different time intervals based on heat accumulation effect . To estimate the resistance tuning in PCM cell with pre‐ and post‐synaptic spikes, the temperature development is studied.…”
Section: Resultsmentioning
confidence: 99%